2019
DOI: 10.1111/nph.16200
|View full text |Cite
|
Sign up to set email alerts
|

The H3K4 demethylase Jar1 orchestrates ROS production and expression of pathogenesis‐related genes to facilitate Botrytis cinerea virulence

Abstract: Histone 3 Lysine 4 (H3K4) demethylation is ubiquitous in organisms, however the roles of H3K4 demethylase JARID1(Jar1)/KDM5 in fungal development and pathogenesis remain largely unexplored. Here, we demonstrate that Jar1/KDM5 in Botrytis cinerea, the grey mould fungus, plays a crucial role in these processes.The BcJAR1 gene was deleted and its roles in fungal development and pathogenesis were investigated using approaches including genetics, molecular/cell biology, pathogenicity and transcriptomic profiling.Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 76 publications
(117 reference statements)
1
40
0
Order By: Relevance
“…Endogenous ROS and the cAMP signalling pathway play crucial roles in B. cinerea infection-related development, including conidial germination and IFS formation (Marschall and Tudzynski, 2016b;Feng et al, 2017;Hou et al, 2020). Our data indicated that disruption of BcCGF1 impairs the pathogen conidial germination, IFS formation, host penetration, and virulence (Figures 3-6).…”
Section: Loss Of Bccgf1 Impairs Endogenous Ros Production and Camp mentioning
confidence: 67%
See 4 more Smart Citations
“…Endogenous ROS and the cAMP signalling pathway play crucial roles in B. cinerea infection-related development, including conidial germination and IFS formation (Marschall and Tudzynski, 2016b;Feng et al, 2017;Hou et al, 2020). Our data indicated that disruption of BcCGF1 impairs the pathogen conidial germination, IFS formation, host penetration, and virulence (Figures 3-6).…”
Section: Loss Of Bccgf1 Impairs Endogenous Ros Production and Camp mentioning
confidence: 67%
“…DAB is converted to dark-brown polymers in the presence of H 2 O 2 and NBT forms a dark-blue water-insoluble formazan precipitate on reduction by superoxide radicals. We also determined the influence of cAMP signalling on conidial germination and/or IFS formation of the tested strains as previously described (Feng et al, 2017;Cao et al, 2018;Hou et al, 2020). Our data demonstrate that the ∆Bccgf1 mutants are difficult to be stained in the germ-tubes and growing mycelia during conidial germination, appressorium, and infection structure formation (Figures 8a and S7); quantification analysis indicated that the relative ROS production by the mutants was significantly reduced (Figure 8b).…”
Section: Loss Of Bccgf1 Impairs Endogenous Ros Production and Camp mentioning
confidence: 70%
See 3 more Smart Citations